2020
DOI: 10.3390/w12092385
|View full text |Cite
|
Sign up to set email alerts
|

Lag Time as an Indicator of the Link between Agricultural Pressure and Drinking Water Quality State

Abstract: Diffuse nitrogen (N) pollution from agriculture in groundwater and surface water is a major challenge in terms of meeting drinking water targets in many parts of Europe. A bottom-up approach involving local stakeholders may be more effective than national- or European-level approaches for addressing local drinking water issues. Common understanding of the causal relationship between agricultural pressure and water quality state, e.g., nitrate pollution among the stakeholders, is necessary to define realistic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Nitrate is stable in the upper oxic part of aquifers and may take decades before it reaches drinking water abstraction wells. This means that nitrogen mitigation measures at the agricultural fields can also take decades to reduce the nitrate concentrations in groundwaterbased drinking water (Kim et al 2020;Hansen et al 2017;Dalgaard et al 2014;NRC 1995). In Denmark, drinking water is entirely based on groundwater and in most cases only undergoes simple water treatment such as aeration and sand-filtration (Schullehner and Hansen 2014).…”
Section: Nitrate (No −mentioning
confidence: 99%
“…Nitrate is stable in the upper oxic part of aquifers and may take decades before it reaches drinking water abstraction wells. This means that nitrogen mitigation measures at the agricultural fields can also take decades to reduce the nitrate concentrations in groundwaterbased drinking water (Kim et al 2020;Hansen et al 2017;Dalgaard et al 2014;NRC 1995). In Denmark, drinking water is entirely based on groundwater and in most cases only undergoes simple water treatment such as aeration and sand-filtration (Schullehner and Hansen 2014).…”
Section: Nitrate (No −mentioning
confidence: 99%
“…Future research is also required to establish new criteria and more efficient optimization techniques to identify the key parameters of NPS pollutants, such as the time lag index [26], and incorporate them into the PTRFFM to realize a better representation of the whole process of NPS pollutant transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the nutrient export behaviour in streams draining Nordic mini-catchments seems to be dominantly controlled by their land use characteristics and, to a lesser extent, their climate. Kim et al [33] investigated lag time as an indicator of the link between nitrogen (N) surplus in agriculture and groundwater nitrate concentrations utilizing a cross correlation analysis method. The authors used groundwater monitoring data from three case study sites with groundwater-based drinking water abstraction: Tunø and Aalborg-Drastrup in Denmark and La Voulzie in France.…”
Section: New Technologies For Monitoring Mapping and Analysing Water Qualitymentioning
confidence: 99%
“…In these case study sites, soil surface N surplus and long-term groundwater monitoring data were available for the analysis. Kim et al [33] found that for Tunø and La Voulzie, where matrix flow is the dominant groundwater pathway, the N lag times continuously increased with an increasing distance from the agricultural N source (in Tunø: from 0 to 20 years between 1.2 to 24 m below the land surface (mbls); at La Voulzie: from 8 to 24 years along the groundwater pathway). However, in Aalborg-Drastrup where both matrix and fracture flows are important groundwater pathways, the N lag times showed a greater variability with depth: for instance, a 23-year lag time at 9-17 mbls compared to a 4-year lag time at 21-23 mbls.…”
Section: New Technologies For Monitoring Mapping and Analysing Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation